Influence of Different Planting Schemes and Nitrogen Fertilizer Rates on the Growth and Development of Rice - G‘afurjanovna, Muminova Muxabbat (American Journal of Biology and Natural Sciences, 2025)
In this article, the influence of feeding rates and planting schemes on the growth and development processes of the "Billur" rice variety was studied. During the study, various agrotechnical variants were compared and their influence on plant height was assessed. Under these conditions, due to the density of plant density, the need for light increases, which contributes to the growth of plant height. The research results have practical significance for this variety.